Changes in right heart haemodynamics and echocardiographic function in an advanced phenotype of pulmonary hypertension and right heart dysfunction associated with pulmonary fibrosis. Issue 2 (15th January 2014) - Saggar, Rajeev; Khanna, Dinesh; Vaidya, Anjali; Derhovanessian, Ariss; Maranian, Paul; Duffy, Erin; Belperio, John A; Weigt, Sam S; Dua, Shiv; Shapiro, Shelley S; Goldin, Jonathan G; Abtin, Fereidoun; et al.
Abstract : Background: Pulmonary hypertension (PH)-targeted therapy in the setting of pulmonary fibrosis (PF) is controversial; the main clinical concern is worsening of systemic hypoxaemia. We sought to determine the effects of gentle initiation and chronic administration of parenteral treprostinil on right heart function in patients with PF associated with an advanced PH phenotype. Methods: Open-label, prospective analysis of patients with PF-PH referred for lung transplantation (LT). Advanced PH was defined as mean pulmonary artery pressure (mPAP) ≥35 mm Hg. We compared haemodynamics, Doppler echocardiography (DE), oxygenation, dyspnoea and quality of life indices, and 6 min walk distance (6MWD) before and 12 weeks after parenteral treprostinil. Results: 15 patients were recruited in the study. After therapy, there were significant improvements in right heart haemodynamics (right atrial pressure (9.5 ± 3.4 vs 6.0 ± 3.7); mPAP (47 ± 8 vs 38.9 ± 13.4); CI (2.3 ± 0.5 vs 2.7 ± 0.6); pulmonary vascular resistance (698 ± 278 vs 496 ± 229); transpulmonary gradient (34.7 ± 8.7 vs 28.5 ± 10.3); mvO2 (65 ± 7.2 vs 70.9 ± 7.4); and stroke volume index (29.2 ± 6.7 vs 33 ± 7.3)) and DE parameters reflecting right heart function (right ventricular (RV) end diastolic area (36.4 ± 5.2 vs 30.9 ± 8.2 cm 2 ), left ventricular eccentricity index (1.7 ± 0.6 vs 1.3 ± 0.5), tricuspid annular planar systolic excursion (1.6 ± 0.5 vs 1.9 ± 0.2 cm)). These changes occurred without significant alteration in systemic oxygenation, heart rate, or mean systemic arterial pressure. In addition, improvements were seen in 6MWD (171 ± 93 vs 230 ± 114), 36-Item Short Form Health Survey Mental Component Summary aggregate (38 ± 11 vs 44.2 ± 10.7), University of California, San Diego Shortness of Breath Questionnaire (87 ± 17.1 vs 73.1 ± 21), and brain natriuretic peptide (558 ± 859 vs 228 ± 340). Conclusions: PH-targeted therapy may improve right heart haemodynamics and echocardiographic function without affecting systemic oxygen saturation in an advanced PH phenotype associated with RV dysfunction in the setting of PF.